Bone health of immigrant Chinese women living in New York City. - Babbar, R; Handa, AB; Lo, C; Guttmacher, S; Shindledecker, R; Chung, W; Fong, C; Ho-Asjoe, H; Chan-Ting, R; Dixon, L (2006)
Osteoporosis is a serious national and global public health problem, but data on bone health are limited for Asian women living in the U.S., the majority of whom are Chinese. For this study, we measured bone mineral density (BMD) by dual energy X-ray densitometry (DXA) at the lumbar spine and hip region in 300 immigrant Chinese women, ages 40-90 y, living in New York City. We also collected demographic and health data, information about knowledge and care for osteoporosis, and anthropometric measures, and estimated calcium intake from the women. In our sample, 55% had osteoporosis and 38% had low bone mass (osteopenia). Older age, lower body mass index (BMI), and shorter height were associated with lower BMD at all sites. Years lived in the U.S. and number of children were also associated with lower BMD of the lumbar spine. Chinese women who emigrated from Mainland China had lower BMD at the lumbar spine and femoral neck than Chinese women who emigrated from Hong Kong, after adjusting for potential confounders. Both groups of immigrant women had lower BMD at all sites than a national sample of U.S. Caucasian women. Although the women in our study had generally poor knowledge about osteoporosis, most could identify at least one food rich in calcium. The large number of immigrant Chinese women in New York City with osteoporosis calls for major efforts to increase awareness, prevention, diagnosis, and treatment of this condition in this susceptible population.